2020
DOI: 10.1177/1177180120956718
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic challenges faced by traditional healers in Limpopo province of South Africa: conversations from below

Abstract: Traditional healing remains core to many local communities in South Africa. This research was aimed at fostering stronger relationships between traditional healers and biomedical medicine focusing on their socio-economic challenges. This research involved collaboration between two Universities in South Africa and the USA, focusing on the social welfare and traditional healing, by articulating the experiences and positions of 40 selected traditional healers. Afro-sensed and developmental social welfare approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Snowball sampling was used to identify the 63 subsequent herbalists in their networks [ 35 ]. Rapport was created with the herbalists by researchers through establishment of cordial interpersonal interactions on the intentions of the study [ 36 ]. Field excursions were undertaken with the help of the herbalists to locate the medicinal plants in their habitats.…”
Section: Methodsmentioning
confidence: 99%
“…Snowball sampling was used to identify the 63 subsequent herbalists in their networks [ 35 ]. Rapport was created with the herbalists by researchers through establishment of cordial interpersonal interactions on the intentions of the study [ 36 ]. Field excursions were undertaken with the help of the herbalists to locate the medicinal plants in their habitats.…”
Section: Methodsmentioning
confidence: 99%
“…The Madagascar issue is a typical example of how the Westerners have negatively looked at IKS as possible remedies to ailments. Commenting on the attitudes of modern health systems on IKS, Masoga and Shokane (2020) and Rugwiji (2019Rugwiji ( , 2008 postulated that "…the African way of dealing with ailments are perceived as evil and satanic." However, this chapter makes use of a plethora of ethno-medical testimonies by people who claim to have used IKS as remedies to curb COVID-19.…”
Section: African Response To Pandemics: a Literature Reviewmentioning
confidence: 99%
“…There are different studies related to the current study which scrutinize indigenous healing from the South African context. Amongst those studies, Masoga and Shokane (2020) looked at socioeconomic challenges faced by traditional healers in the Limpopo province of South Africa. The study findings suggest that, even though it was confirmed that traditional healing remained core to many local communities in South Africa, most traditional healers experience the ravages of poverty and unemployment.…”
Section: Introductionmentioning
confidence: 99%